Regression Coefficient Derivation via Fractional Calculus Framework - Muath Awadalla; Yves Yannick Yameni Noupoue; Yucel Tandogdu; Kinda Abuasbeh (Journal of Mathematics)
This study focuses on deriving coefficients of a simple linear regression model and a quadratic regression model using fractional calculus. The work has proven that there is a smooth connection between fractional operators and classical operators. Moreover, it has also been shown that the least squares method is classically used to obtain coefficients of linear and quadratic models that are viewed as special cases of the more general fractional derivative approach which is proposed.